Through the Darkness of Future Past’: How Twin Peaks: The Return Transformed Television - KABAK, MURAT (My University, 2018)
From The Fuller House to The X-Files and to Star Wars, cinema and television have witnessed a surge of revivals, remakes and continuations in the last decade. The obsession with the nostalgia and recapturing the past are so permeated into our visual culture that even Charlie Brooker's futuristic satire / technotopia Black Mirror had its fourth season premiere with an homage to Star Trek. As Laura Palmer promised to see Agent Cooper in 25 years in the first episode of Twin Peaks, the creators of the show, David Lynch and Mark Frost have revived the series 27 years after its final episode. Yet, the third season of Twin Peaks has managed to avoid the pitfalls of a revival through its deconstruction of memory and nostalgia. As the literature written on the first two seasons of Twin Peaks showed, the series has reinvented the television series both in terms of its genre and its distinct visual style. The focus of this paper; however, is the third season of the show and with an emphasis on the 8th, 22nd and 23rd episodes, this paper aims to analyze how the show's creators played with the viewer expectations to emphasize the impossibility of recapturing the past. I argue that Twin Peaks: The Return is a critique of a culture that is obsessed with nostalgia. Through the 18-hours third season of the show, the creators Lynch and Frost have not only transformed the series itself but our understanding of revivals and remakes.